A Retrospective Cohort Study on the Preliminary Efficacy of Massage Therapy for Chemotherapy-Induced Peripheral Neuropathy Among Cancer Patients - Mingxiao Yang MD(CMD), PhD; Cassie Shao; Carrie Shao; Kirin Saint MD; Mira Gupta; Rocco Caputo LMT, CNMT; Mary Lou Galantino MS, PhD, MSCE; Steven Harte PhD; Ting Bao MD, MS (Integrative Cancer Therapies)
Purpose: Chemotherapy-induced peripheral neuropathy (CIPN) worsens the quality of life for people with cancer. Massage therapy involves neuromuscular modulations and can potentially reduce CIPN symptoms. We examined the immediate improvements in CIPN-related pain and neuropathy following massage therapy among patients with CIPN. Methods: In a retrospective cohort, we assessed patients who received 1 massage therapy session for CIPN symptom relief during or after chemotherapy at a National Cancer Institute-Designated Comprehensive Cancer Center from October 2017 to September 2022. We measured the severity of pain and neuropathy before and after massage therapy with a 4-item verbal rating scale (VRS) or a 0 to 10 numerical rating scale (NRS). We converted NRS to VRS scores and examined the pre-post differences in symptom severity using the Wilcoxon rank test. Results: Among 23 patients (median [range] age 64 [4-85] years, female 74%, White 70%), one session of massage therapy decreased the percentage of patients reporting moderate-to-severe pain from 81% at baseline to 0% (none) post-massage; percentage of patients reporting neuropathy also reduced from 77% at baseline to 12% following treatment. The pre-post differences were statistically significant for both pain (mean: −1.6, 95% confidence interval [CI] −1.9 to −1.2; P  = .001) and neuropathy scores (mean: −1.2, 95%CI −1.4 to −0.9; P  < .0001). Conclusion: Among cancer patients with CIPN, one session of massage therapy was associated with immediate neuropathy and CIPN pain relief reported by patients following treatment. However, this preliminary finding requires further rigorous verifications in future randomized controlled clinical trials.